Piezoelectric element
By setting multiple stress relief parts in the piezoelectric element, the stress concentration problem caused by the high stiffness of lead-free piezoelectric ceramic materials is solved, and effective stress dispersion and durability are achieved.
Patent Information
- Application Number
- CN202480005376.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-01
- Filing Date
- 2024-08-20
- Publication Date
- 2025-08-29
AI Technical Summary
Lead-free piezoelectric ceramic materials have high stiffness, and the problem of stress concentration in piezoelectric components cannot be fully alleviated by setting slits alone.
In the piezoelectric element, a plurality of stress relief parts are formed, the stress relief parts are located on the center side of the slit, and the curved or sloped surface shape is used to disperse the stress, in combination with the use of lead-free piezoelectric ceramic composition.
It effectively alleviates stress concentration in piezoelectric components, improves durability and stress dispersion effects.
Smart Images

Figure CN120570100A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a piezoelectric element. Background Art
[0002] In the past, PZT (lead zirconate titanate) was widely used as a ceramic exhibiting piezoelectricity. The piezoelectric body composed of PZT expands and contracts according to the applied voltage, and a stacked piezoelectric driver element with a structure in which a plurality of piezoelectric bodies and internal electrodes are alternately stacked has been developed and put into practical use. In the stacked piezoelectric driver element, the portion of the piezoelectric body clamped by the internal electrodes becomes a polarized area, and the portion not clamped by the internal electrodes becomes a non-polarized area. Therefore, at the junction of the polarized area and the non-polarized area, the displacement distribution changes significantly, and stress is concentrated in this part. Due to this stress concentration, if the drive is carried out for a long time, the possibility of cracks increases and the durability is reduced.
[0003] To alleviate such stress, a stacked piezoelectric actuator element is known in which slits are formed on the side surfaces of a stacked body in a direction perpendicular to the stacking direction (parallel to the stacking surface). For example, Japanese Patent Application Publication No. 2009-131138 (hereinafter referred to as Patent Document 1) discloses a stacked piezoelectric actuator element having a columnar shape formed by alternately stacking a plurality of piezoelectric layers and internal electrodes. The stacked body has: a plurality of slits formed on opposite side surfaces of the stacked body, extending into the interior of the piezoelectric layers and formed at arbitrary intervals along the stacking direction of the stacked body; and side electrodes formed on opposite side surfaces of the stacked body, separated by the slits, and electrically connected to the internal electrodes.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 2009-131138 Summary of the Invention
[0007] Problems to be solved by the invention
[0008] However, PZT contains lead, which poses an environmental concern. In recent years, lead-free piezoelectric ceramics have been developed as an example of lead-free ceramic materials. However, lead-free piezoelectric ceramics are less deformable and more rigid than PZT, so simply providing slits may not provide sufficient stress relief. In other words, the stress in the slit-containing portion of the piezoelectric element may not be adequately relieved.
[0009] Solutions for solving problems
[0010] The piezoelectric element of the present invention is formed by alternatingly stacking multiple layers of piezoelectric bodies and electrodes having piezoelectric properties, wherein at least one of the piezoelectric bodies has a slit on its side surface, and the outer edge of the cross-section of the portion of the piezoelectric element having the slit when cut in a direction perpendicular to the stacking direction has multiple sides and multiple stress relief portions connecting an adjacent pair of the sides, respectively. The stress relief portions are formed so that, when the point where the portions formed by extending the adjacent pair of the sides intersect is set as an imaginary vertex, the slit is located closer to the center side of the piezoelectric body than the imaginary vertex.
[0011] Effects of the Invention
[0012] According to the present invention, stress in a portion of the piezoelectric element having a slit can be alleviated. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 It is a cross-sectional view schematically showing the structure of a piezoelectric element according to an embodiment.
[0014] Figure 2 It is a perspective view showing a part of the stacked body exploded in the stacking direction.
[0015] Figure 3 It is a cross-sectional view showing the periphery of the slit in an enlarged manner.
[0016] Figure 4 This is a diagram showing a cross section of a portion having a slit in a piezoelectric element, taken along a direction perpendicular to the stacking direction.
[0017] Figure 5 This is a cross-sectional view showing, by simulation, how stress acts on a cross section passing through a slit.
[0018] Figure 6 This is a graph showing the maximum stress acting on the vertex versus R / (L1 / 2).
[0019] Figure 7 This is a graph showing the stress difference between vertices and edges relative to L1 / L2.
[0020] Figure 8 This is a diagram showing the process flow of a piezoelectric element.
[0021] Figure 9 This is a cross-sectional photograph of the slit. DETAILED DESCRIPTION
[0022] [Overview of Embodiments]
[0023] First, embodiments of the present invention will be described below.
[0024] (1) The piezoelectric element of the present invention is formed by alternately stacking a plurality of layers of piezoelectric bodies and electrodes having piezoelectric properties, wherein at least one of the piezoelectric bodies has a slit on its side surface, and the outer edge of a cross-section of the portion of the piezoelectric element having the slit when cut in a direction perpendicular to the stacking direction has a plurality of sides and a plurality of stress relief portions connecting adjacent pairs of the sides, wherein the stress relief portions are formed such that, when a point where portions extending from the adjacent pair of sides intersect is defined as an imaginary vertex, the slit is located closer to the center of the piezoelectric body than the imaginary vertex. The piezoelectric body can be formed, for example, of a lead-free piezoelectric ceramic composition.
[0025] The portion of the piezoelectric body sandwiched between the electrode and the adjacent electrode becomes a polarized region, and the portion not sandwiched between the two electrodes becomes a non-polarized region. It is known that at the boundary between the polarized region and the non-polarized region, the displacement distribution changes significantly, and stress is concentrated in this portion. In particular, piezoelectric bodies formed from lead-free piezoelectric ceramic compositions are difficult to deform and have greater rigidity than PZT, so it is believed that stress cannot be fully relieved by simply forming slits. Therefore, according to the above structure, multiple stress relief portions are formed on the basis of forming slits, thereby being able to relieve stress.
[0026] (2) Preferably, the stress relaxation portion is formed of a sloped C-surface.
[0027] Since the stress relaxation portion is formed of the C-surface, stress can be easily dispersed over the entire C-surface.
[0028] (3) Preferably, the stress relief portion is formed of an R-surface having a curved shape.
[0029] Since the stress relaxation portion is formed of the R-surface, stress can be easily dispersed over the entire R-surface.
[0030] (4) Preferably, when the edge connecting adjacent imaginary vertices is set as an imaginary edge, the length of the imaginary edge is set as L1, and the length of the area in which the stress relief portion is formed on the imaginary edge is set as R, R / (L1 / 2) is greater than 15% and less than 100%.
[0031] According to the above configuration, the maximum stress acting on the stress relieving portion can be reduced.
[0032] (5) The piezoelectric element of the present invention is formed by alternately stacking a plurality of layers of piezoelectric bodies having piezoelectric properties and electrodes, wherein at least one of the piezoelectric bodies has a slit in its side surface, and the outer edge of a cross-section of the portion of the piezoelectric element having the slit, when cut in a direction perpendicular to the stacking direction, is circular or elliptical. The piezoelectric body can be formed, for example, from a lead-free piezoelectric ceramic composition.
[0033] (6) Preferably, a plurality of the slits are formed at arbitrary intervals in the stacking direction and every 35 layers or less.
[0034] [Details of Implementation Methods]
[0035] Hereinafter, specific examples of the present invention will be described with reference to the accompanying drawings. However, the present invention is not limited to these examples, but is defined by the claims, and is intended to include all modifications within the meaning and scope of the claims.
[0036] <Implementation Method>
[0037] pass Figures 1 to 9 The embodiments of the present invention are described below. Figure 1 As shown in FIG. 1 , the piezoelectric element 1 includes a stacked body 5 formed by alternately stacking a plurality of piezoelectric bodies 2 formed of a lead-free piezoelectric ceramic composition having piezoelectricity and conductive internal electrodes 3 and 4. Figure 1 In the figure, the number of stacked layers 5 is omitted and shown as small, but in the actual piezoelectric element 1, for example, Figure 3 As shown, there are many stacking numbers.
[0038] [Piezoelectric body 2]
[0039] The piezoelectric body 2 is a lead-free piezoelectric ceramic composition having a main phase formed of a first crystal phase composed of an alkali niobate perovskite-type oxide and a subphase including a second crystal phase composed of an M-Ti-O-based spinel compound.
[0040] In this specification, the term "spinel compound" includes both normal spinel compounds having a normal spinel crystal structure and inverse spinel compounds having an inverse spinel crystal structure. The element M in the M-Ti-O spinel compound is a monovalent to tetravalent metal element.
[0041] In addition, the proportion of the second crystal phase in the lead-free piezoelectric ceramic composition is greater than 0 volume % and less than 10 volume %, and the remainder is the first crystal phase. In this specification, the first crystal phase is also referred to as the "main phase," and crystal phases other than the main phase are referred to as "subphases."
[0042] The first crystal phase of the alkali niobate perovskite-type oxide is represented by the following composition formula (1).
[0043] (K a Na b Li c C d ) e (D f E g )O h ·····(1)
[0044] Among them, element C is at least one of Ca (calcium) and Ba (barium), element D is at least one of Nb (niobium), Ti (titanium), and Zr (zirconium) including Nb, and element E is at least one of Fe (iron), Co (cobalt), Zn (zinc), and Mg (magnesium).
[0045] In the above composition formula (1), K (potassium), Na (sodium), Li (lithium), and element C are located at the so-called A site of the perovskite structure. Element D and element E are located at the so-called B site of the perovskite structure.
[0046] As the values of the coefficients a, b, c, d, e, f, g, and h in the above composition formula (1), the electrical properties or piezoelectric properties (particularly the piezoelectric constant d) of the lead-free piezoelectric ceramic composition are selected from the values that establish the perovskite structure. 33 ), and a preferred value from the viewpoint of suppressing the sintering temperature during production to a low level is selected.
[0047] Specifically, the sum of the coefficients a, b, c, and d of the elements at the A site is 1 (ie, a+b+c+d=1).
[0048] The coefficients a, b, and c are preferably 0 ≤ a < 1, 0 ≤ b < 1, and 0 ≤ c < 1, respectively. However, the ideal a = b = c = 0 (i.e., a lead-free piezoelectric ceramic composition containing no K, Na, or Li) does not hold. For the coefficients a and b of K and Na, the typical values are 0 < a ≤ 0.6 and 0 < b ≤ 0.6. The coefficient c of Li can be 0 (zero), but is preferably 0 < c ≤ 0.2, and more preferably 0 < c ≤ 0.1.
[0049] The coefficient d of the element C may be 0 (zero), but is preferably 0<d≤0.2, and more preferably 0<d≤0.1.
[0050] The coefficient e for the entire A site is any value within a range that does not impair the purpose of the present invention. The coefficient e is preferably 0.80≤e≤1.10, more preferably 0.84≤e≤1.08, and even more preferably 0.88≤e≤1.07.
[0051] The sum of the coefficients f and g of the elements D and E at the B site is 1 (i.e., f + g = 1). In addition, the coefficient f of the element D is preferably not 0 (zero), and the coefficient g of the element E may be 0 (zero) within a range not impairing the purpose of the present invention.
[0052] The oxygen (O) coefficient h is an arbitrary value that allows the first crystalline phase to maintain a perovskite-type crystal structure. A typical value for the coefficient h is approximately 3, with 3.0 ≤ h ≤ 3.1 being preferred. Furthermore, the value of the coefficient h can be calculated based on the electroneutrality condition of the composition of the first crystalline phase. However, compositions that slightly deviate from the electroneutrality condition are also acceptable for the composition of the first crystalline phase.
[0053] The alkali niobate perovskite oxide represented by the above composition formula (1) is an oxide containing K, Na, and Nb as its main metal components, and is therefore called "KNN" or "KNN material." Such alkali niobate perovskite oxides have excellent piezoelectric and electrical properties.
[0054] The second crystal phase M-Ti-O spinel compound is an oxide containing the element M (a monovalent to tetravalent metal element) and Ti (titanium), and is represented by the following composition formula (2), for example.
[0055] M x TiO y ·····(2)
[0056] Here, the element M is a monovalent to tetravalent metal element. Specifically, the element M includes at least one selected from the group consisting of Li, Fe, Co, Zn, Zr, and Mg.
[0057] The coefficients x and y are relative values when the Ti content is set to 1. In order for the second crystal phase to form a spinel compound, the coefficient x preferably satisfies 0.5≤x≤5.0. The coefficient y is an arbitrary value that forms a spinel compound, and preferably satisfies, for example, 2≤y≤8.
[0058] The second crystal phase composed of a spinel compound stabilizes the structure of the first crystal phase, thereby achieving a lead-free piezoelectric ceramic composition with excellent piezoelectric properties. Furthermore, from the perspective of piezoelectric properties, it is preferred to use a second crystal phase represented by the composition formula M2TiO4 or (M1, M2)TiO4 containing two divalent metal elements M.
[0059] The second crystal phase lacks piezoelectric properties, but its intermixing with the first crystal phase improves the sinterability of the lead-free piezoelectric ceramic composition, enhancing its structural stability and improving its piezoelectric properties. Specifically, the second crystal phase fills the pores formed between crystals of the first crystal phase. As a result, crystals of the first crystal phase are bonded together via the second crystal phase, presumably resulting in improved structural stability and piezoelectric properties of the lead-free piezoelectric ceramic composition.
[0060] [Internal electrodes 3, 4]
[0061] like Figure 2As shown, the internal electrodes 3 and 4 are alternately arranged in the stacking direction, with a single piezoelectric body 2 sandwiched between the internal electrodes 3 and 4. The internal electrodes 3 are electrodes of the same polarity (e.g., positive), while the internal electrodes 4 are electrodes of the same polarity (e.g., negative). The internal electrodes 3 and 4 of opposite polarities are spaced apart in the stacking direction to prevent electrical short circuits.
[0062] One side of the internal electrode 3 ( Figure 1 The left side in the middle) is formed on one side of the stacked body 5 ( Figure 1 The other side of the internal electrode 3 ( Figure 1 The right side in the middle) is formed so as not to be on the other side of the stacked body 5 ( Figure 1 The side (right side in the middle) is exposed.
[0063] One side of the internal electrode 4 ( Figure 1 The right side in the middle) is formed on the other side of the stacked body 5 ( Figure 1 The other side of the internal electrode 4 ( Figure 1 The left side in the middle) is formed so as not to be on one side of the stacked body 5 ( Figure 1 The left side is exposed.
[0064] By configuring the internal electrodes 3 and 4 in this manner, the internal electrodes 3 and 4 of different polarities are prevented from being electrically short-circuited with each other.
[0065] [Slit 6]
[0066] The slits 6 are formed on the outer peripheral side surface of the stacked body 5 in a manner extending perpendicularly to the stacking direction (parallel to the stacking surface) and penetrating to a predetermined depth from the outer peripheral side surface. Figure 1 As shown, the depth of the slit 6 from the outer peripheral side surface of the laminate 5 is set deeper than the end portions of the internal electrodes 3 and 4 . Figure 9 The actual cross-sectional photograph shows the slits 6. A plurality of slits 6 are formed at arbitrary intervals in the stacking direction and every 35 layers or less. These slits 6 are formed to relieve stress applied when the piezoelectric element 1 is driven.
[0067] [Side electrodes 7, 8]
[0068] Side electrodes 7 and 8 are formed on both sides of the laminate 5. These side electrodes 7 and 8 are formed by patterning a conductive paste by screen printing or the like, and are separated into blocks divided by slits 6 in the lamination direction.
[0069] [External electrodes 11, 12]
[0070] Solder layers 9 and 10 are formed on the surfaces of the side electrodes 7 and 8. A pair of external electrodes 11 and 12 are fixed to the side electrodes 7 and 8 via these solder layers 9 and 10. This provides electrical continuity between the side electrodes 7 and 8 in each block divided by the slits 6 in the stacking direction. External electrodes 11 and 12 are formed from a conductive member (e.g., copper). They are formed, for example, in a mesh shape and are capable of deforming in response to the expansion and contraction of the stack 5.
[0071] [Lead electrodes 13, 14]
[0072] In addition, in the side electrodes 7 and 8, Figure 1 Lead electrodes 13 and 14, serving as voltage supply members for externally supplying voltage, are fixed to the side electrodes 7 and 8 of the lowermost block portion via solder layers 9 and 10. Because lead electrodes 13 and 14 are fixed to side electrodes 7 and 8, even when the laminate 5 vibrates at high speed for a long period of time, the external electrodes 11 and 12 will not break due to the inertial weight of lead electrodes 13 and 14.
[0073] The laminate 5 is formed by alternately stacking a plurality of layers of piezoelectric bodies 2 and internal electrodes 3 and 4. The laminate 5 comprises polarized regions 50 that are displaced by application of voltage to the internal electrodes 3 and 4, and non-polarized regions 51 that are not displaced. The non-polarized regions 51 are located below, above, and around the polarized regions 50.
[0074] Laminated body 5 Figure 1 The lower side of the lead electrode 13 is fixed, becoming a fixed end that does not move, while the upper side becomes a movable end that moves. Lead electrodes 13 and 14 are fixed to side electrodes 7 and 8 of the block portion located at the end portion on the fixed end side. In other words, lead electrodes 13 and 14 are fixed to side electrodes 7 and 8 on the fixed end side relative to slit 6 closest to the fixed end side.
[0075] [Stress relief portion 30]
[0076] Figure 4 It is a cross section when the portion of the stacked body 5 having the slit 6 is cut in a direction perpendicular to the stacking direction. Figure 4 The portion shown with hatching in the center is the piezoelectric body 2 connecting the piezoelectric body 2 above the slit 6 and the piezoelectric body 2 below the slit 6 , and is hereinafter referred to as a connecting portion 15 .
[0077] The outer edge of the cross-section of the connecting portion 15 has four sides 20 and four stress-relieving portions 30 that connect a pair of adjacent sides 20 respectively. The stress-relieving portion 30 is formed such that when the point where the portions 21 formed by extending a pair of adjacent sides 20 respectively intersect is set as the imaginary vertex 22, the slit 6 is located on the side closer to the center of the piezoelectric body 2 than the imaginary vertex 22. The cross-section of the connecting portion 15 in the present embodiment is substantially square, but it may also be substantially triangular or a substantially polygon with five or more sides.
[0078] The stress-relieving portion 30 of the embodiment is constituted by an R surface having a curved surface shape, but it may also be constituted by a C surface having a slope shape. In addition, the outer edge of the connecting portion 15 of the embodiment is constituted by a straight-line-shaped side 20 and a circular-shaped (quarter-circle shape) stress-relieving portion 30, but an elliptical-shaped stress-relieving portion may be provided instead of the circular-shaped stress-relieving portion 30.
[0079] [Examples]
[0080] The process flow of the piezoelectric element 1 is shown in Figure 8 . First, various raw material powders required for forming the main phase are prepared, and these raw material powders are weighed according to the values of the coefficients a, b, c, d, e, f, g in the composition formula of the main phase so as to achieve the target composition. The weighed raw material powders are pulverized and mixed by a dry vibration mill for 4 hours or more to obtain a mixed powder. The obtained mixed powder is pre-baked for 1 hour to 10 hours under a temperature condition of 600°C to 1200°C in an atmospheric atmosphere, for example, to obtain a powdery main-phase pre-baked product.
[0081] In addition, various raw material powders required for forming the sub-phase are prepared, and these raw material powders are weighed according to the value of the coefficient x in the composition formula of the sub-phase so as to achieve the target composition. The weighed raw material powders are pulverized and mixed by a dry vibration mill for 4 hours or more to obtain a mixed powder. The obtained mixed powder is pre-baked for 1 hour to 10 hours under a temperature condition of 600°C to 1200°C in an atmospheric atmosphere, for example, to obtain a powdery sub-phase pre-baked product (powder production).
[0082] Next, a dispersant, a binder, and an organic solvent (such as toluene) are added to the obtained main-phase pre-baked product and sub-phase pre-baked product, and their wet mixture is pulverized and mixed to obtain a slurry. After that, casting sheet forming (Japanese: キャスティングシート成型) is performed to process the slurry into a sheet shape, thereby producing a ceramic green sheet (hereinafter simply referred to as "green sheet") with a specified thickness (sheet forming).
[0083] Next, the green sheet is punched into a 150 mm long x 150 mm wide square, and an electrode layer to become an internal electrode is formed on one side of the green sheet using a conductive paste for internal electrodes (Pt paste) by, for example, screen printing (internal electrode printing).
[0084] Next, a predetermined number of green sheets (non-driving layers) without printed electrode layers and green sheets (driving layers) with printed electrode layers are stacked in sequence, pressure-bonded and laminated under temperature and pressure, and then cut into small pieces. For example, pressure bonding and lamination are performed at a temperature of 40°C to 80°C and a pressure of 5MPa to 100MPa.
[0085] The element cut into small pieces is kept at a temperature of 500° C. to 800° C. in an air atmosphere for 2 to 100 hours to perform a binder removal treatment (degreasing).
[0086] The element after the binder removal treatment is sintered (fired) by maintaining it at a temperature of 900° C. to 1400° C. for 1 to 100 hours in an air atmosphere, for example.
[0087] Next, the four corners of the fired element are cut to a specified size (for example, a quadrilateral of 6 mm in length and 6 mm in width) to expose the internal electrodes. The upper and lower surfaces of the element are ground, the thickness is adjusted, and the element is processed into a specified parallelism. For elements in the shape of a rectangular parallelepiped, a slit is formed using a laser (manufactured by COHERENT, UV, GREEN, IR wavelength) in a direction orthogonal to its stacking direction. The slit is formed (element processing) in such a way that the radius of curvature of the stress relief portion is 0 mm to 0.2 mm and the length of one side is 1 mm to 5.4 mm.
[0088] Electrodes are then printed on the sides of the stack, sintered and polarized at 600°C to 800°C. Four of the resulting components are assembled using an adhesive, and the side electrodes of each component are connected with solder wires before being sealed in a metal tube (assembly).
[0089] The evaluation process is described below. ANSYS Workbench 2021R2 was used for simulation analysis.
[0090] like Figure 4 As shown, a side connecting adjacent virtual vertices 22 is defined as a virtual side, the length of the virtual side is defined as L1, and the length of a region where the stress relaxation portion 30 is formed on the virtual side is defined as R. Figure 5 The upper section is a cross-sectional view showing the maximum stress acting on the apex (stress relief portion) of the connecting portion 15 when R / (L1 / 2) varies within the range of 0% to 100% by simulation. The locations where stress is applied are indicated by dark colors.
[0091] like Figure 5 As shown in the upper part of , it can be seen that at 0% and 5%, stress acts only on the connecting portion 15. In contrast, at 15% to 100%, stress acts on both the connecting portion 15 and the piezoelectric body 2 adjacent to the upper and lower sides of the connecting portion 15. In other words, at 15% to 100%, the stress is diffusely dispersed across the connecting portion 15 and the piezoelectric body 2, thereby alleviating the stress acting on the connecting portion 15 and reducing the maximum stress.
[0092] like Figure 6 As shown in the figure, it can be seen that the maximum stress is 75 MPa or more when R / (L1 / 2) is 0% and 5% (when the stress relief portion 30 has almost no rounded surface). In contrast, the maximum stress is reduced to 69 MPa when R / (L1 / 2) is 100% (when the stress relief portion 30 has a sufficient rounded surface). The maximum stress relative to R / (L1 / 2) is preferably 15% or more and 100% or less, more preferably 25% or more and 100% or less, further preferably 38% or more and 100% or less, and most preferably 100%.
[0093] like Figure 4 As shown in FIG. 1 , the length of one side of the piezoelectric body 2 adjacent to the upper and lower sides of the connecting portion 15 (the length of one side of the internal electrodes 3 and 4 ) is defined as L2 . Figure 5 The lower section shows a cross-sectional view, based on simulations, showing the stress difference between the vertex (stress relief portion) and the side of the connecting portion 15 when L1 / L2 is varied within a range of 22% to 100%. At 100%, stress concentrates on the connecting portion 15, but at 22% to 74%, stress is diffusely dispersed along the outer edge of the connecting portion 15, thereby relieving the stress on the connecting portion 15 and reducing the stress difference.
[0094] like Figure 7 As shown in the figure, the stress difference is 11 MPa when the L1 / L2 ratio is 100%. In contrast, the stress difference is reduced to less than 2 MPa when the L1 / L2 ratio is 22% to 74%. The stress difference relative to L1 / L2 is preferably 22% to 74%, more preferably 37% to 74%, and most preferably 56%.
[0095] [Effects of the embodiment]
[0096] The piezoelectric element 1 is formed by alternatingly stacking multiple layers of piezoelectric bodies 2 and internal electrodes 3 and 4 formed of a lead-free piezoelectric ceramic composition having piezoelectric properties, wherein at least one of the piezoelectric bodies 2 has a slit 6 on its side surface, and the outer edge of the cross-section of the portion of the piezoelectric element 1 having the slit 6 when cut in a direction perpendicular to the stacking direction has four sides 20 and four stress relief portions 30 respectively connecting an adjacent pair of sides 20, and the stress relief portions 30 are formed so that, when the point where the portions 21 formed by extending the adjacent pair of sides 20 intersect is set as an imaginary vertex 22, the slit 6 is located closer to the center side of the piezoelectric body 2 than the imaginary vertex 22.
[0097] The portion of the piezoelectric body 2 sandwiched between the internal electrode 3 and the adjacent internal electrode 4 becomes the polarized region 50, and the portion not sandwiched between the two electrodes 3 and 4 becomes the non-polarized region 51 on the peripheral side. It is known that at the boundary between the polarized region 50 and the non-polarized region 51 on the peripheral side, the displacement distribution changes significantly, and stress is concentrated in this portion. In particular, the piezoelectric body 2 formed from a lead-free piezoelectric ceramic composition is difficult to deform and has greater rigidity than PZT, so it is believed that the stress cannot be fully relieved by simply forming the slit 6. Therefore, according to the above structure, multiple stress relief portions 30 are formed on the basis of forming the slit 6, so that stress can be relieved.
[0098] Since the stress relief portion 30 is formed of a curved R-surface, stress can be easily dispersed over the entire R-surface.
[0099] When the side connecting adjacent imaginary vertices 22 is defined as an imaginary side, the length of the imaginary side is defined as L1, and the length of the region on the imaginary side where the stress relief portion 30 is formed is defined as R, R / (L1 / 2) is equal to or greater than 15% and equal to or less than 100%. This arrangement can reduce the maximum stress acting on the stress relief portion 30.
[0100] Description of Reference Numerals
[0101] 1. Piezoelectric element; 2. Piezoelectric body; 3. Internal electrode; 4. Internal electrode; 5. Laminated body; 6. Slit; 7. Side electrode; 8. Side electrode; 9. Solder layer; 10. Solder layer; 11. External electrode; 12. External electrode; 13. Lead electrode; 14. Lead electrode; 15. Connecting portion; 20. Side; 21. Portion formed by extending a pair of adjacent sides; 22. Imaginary vertex; 30. Stress relief portion; 50. Polarized region; 51. Non-polarized region.
Claims
1. A piezoelectric element comprising a plurality of layers of alternately stacked piezoelectric bodies and electrodes having piezoelectric properties, wherein: At least one of the piezoelectric bodies has a slit on its side surface. The outer edge of the cross section of the portion of the piezoelectric element having the slit when cut in a direction perpendicular to the stacking direction has a plurality of sides and a plurality of stress relieving portions connecting adjacent pairs of the sides. The stress relieving portion is formed so that, when a point where portions obtained by extending a pair of adjacent sides intersect is defined as a virtual vertex, the slit is located closer to the center of the piezoelectric body than the virtual vertex.
2. The piezoelectric element according to claim 1, wherein The piezoelectric body is formed of a lead-free piezoelectric ceramic composition.
3. The piezoelectric element according to claim 1, wherein The stress relaxation portion is composed of a sloped C-surface.
4. The piezoelectric element according to claim 1, wherein The stress relief portion is formed of an R-surface having a curved shape.
5. The piezoelectric element according to any one of claims 1 to 4, wherein When the side connecting adjacent imaginary vertices is set as an imaginary side, the length of the imaginary side is set as L1, and the length of the area where the stress relief portion is formed on the imaginary side is set as R, R / (L1 / 2) is greater than or equal to 15% and less than or equal to 100%.
6. A piezoelectric element comprising a plurality of layers of alternately stacked piezoelectric bodies and electrodes having piezoelectric properties, wherein: At least one of the piezoelectric bodies has a slit on its side surface. The outer edge of a cross section of a portion of the piezoelectric element having the slit, when cut in a direction perpendicular to the stacking direction, is circular or elliptical.
7. The piezoelectric element according to claim 6, wherein The piezoelectric body is formed of a lead-free piezoelectric ceramic composition.
8. The piezoelectric element according to claim 1 or 6, wherein A plurality of the slits are formed at arbitrary intervals in the stacking direction and every 35 layers or less.
Citation Information
Patent Citations
Laminated type piezoelectric actuator element
JP2009131138A